Análise Bidimensional de alagamentos em Vias Públicas Utilizando Modelagem Hidrológica e Hidráulica - Dutra Júnior, Samuel Almeida (2023)
As a result of disorderly urbanization in cities, the consequent reduction in permeable areas, absence of public cleaning, and the existence of undersized projects, the increase of runoff becomes a urban drainage issue, giving rise to a surge in flooding incidents within urban regions. Within the framework of drainage systems, gutters and storm inlets emerge as noteworthy components deserving attention, as they are the first elements to encounter the generated runoff. The city of Uberlândia serves as a prime example of the repercussions that these phenomena can cause, frequently suffering from floods, negatively impacting the local population. One of the strategies to get a deeper understanding of runoff behavior is hydrodynamic modeling, which enables a reasonably precise estimation of water level formations on urban thoroughfares. In light of this, the primary objective of this research is to propose a methodology that employs both hydrological and hydraulic modeling techniques in a specific section of Uberlândia. The approach utilizes the VBA programming language for Excel and the HEC-RAS software to generate flood maps. Additionally, this study aimed to evaluate the potential benefits arising from increased permeable areas in lots, adhering to municipal guidelines, as well as the installation of storm inlets. Upon generating the flood maps, it was observed that certain regions experienced gutter overflow due to surface runoff. Furthermore, it was evident that incorporating more permeable areas in accordance with municipal regulations did not entirely solve the flooding issue. In terms of the implementation of storm inlets, 14 of them were required to resolve the gutter overflow concerns and to adhere to the water depth limits set by municipal authorities. In conclusion, the methodology presented in this study has proven to be an effective tool in urban drainage planning. It has the capacity to produce pertinent data for a more sustainable approach to prevent and manage floods in urban centers.